Forecasting of Bioethanol Production in the Sudan (University of Khartoum Engineering Journal, 2022)
Gasoline demand of the Sudanese transportation sector is increasing. To meet the demand many measures have been developed in the last few years. These included efficiency improvement and supplement with bioethanol. The latter is blended with gasoline in the range of 5-27%; the blend is also called E85 and E90. The aim of this research was to forecast bioethanol production from molasses of Sudanese Sugar Factories by assuming the design capacities of bioethanol factories in Sudan from 2016 to 2030. Data on current consumption and production of gasoline by refineries as well as the potential production were obtained from relevant sources such as Ministry of Petroleum. The data were analyzed using forecasting models. Mainly two models namely a trend model and an econometric model were used. For econometric model, data on population, gasoline prices and gross domestic product were collected as well, while the trend model is time series dependent only. The results revealed that beyond the year 2021 Sudan production of gasoline will not meet the demand. Bioethanol mixed with gasoline at 10% is a feasible option to supplement gasoline. The study also revealed that the production potential of bioethanol in sugar industry will meet the demand with a surplus in year 2021.